PENGARUH PEMBERIAN TANDA TERIMA KASIH DAN TINGKAT PENDAPATAN APARATUR TERHADAP GRATIFIKASI - Yulius Yulius (Jurnal Good Governance, 2018)
The Governments in carrying out its function, is constrained by gratification practices that conducted with the apparatus, this research aims to discover the influence of people's habits in their gratitude to the gratification; The impact of apparatus’ income level to the gratification;the impact of community habits that show their gratitude and the income levels of the apparatus collectively to the gratification. This research instrument used the questionnaires which distributed to the apparatus, with the conclusion: Community's habits that represent their gratitude for gratification; the income level of the apparatus impact the gratification; the community's habits that represent their gratitude and the apparatus’ income level as together affecting the gratification, even contributing 40.4% of the gratification.Keywords: habit; income; gratification